Sacred cow - Eltit, Diamela, 1949- (London ; New York, NY : Serpent's Tail, 1995)
"Eltit's Vaca sagrada (see HLAS 54:4047), an intense narrative of erotic desire set against the backdrop of political repression in Chile, treats themes of sexual violence, power relationships, the domination of women, and female fantasy. Well translated by Hopkinson. However, this first translation of an Eltit novel includes no locating materials beyond a very short author's biography on the back flap"--Handbook of Latin American Studies, v. 58.
"A paperback original"--P. 4 of cover.